1999
DOI: 10.1021/jp9902809
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for the Photochemical Production of Superoxide by Quinacrine

Abstract: Transient absorption spectroscopy has been used to elucidate the UV-A induced photodynamics of quinacrine. Following excitation of quinacrine in a pH 7.2 buffer solution at 395 nm, the excited molecule ejects an electron into the surrounding aqueous solution. The quantum efficiency for solvated electron formation at this excitation wavelength is determined to be in the range of 0.20−0.40. These results provide a simple mechanism that accounts for the generation of superoxide (O2 -) following UV excitation of q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…During normal oxidative metabolism, the ROS are formed in small quantities and can be removed effectively by natural defense mechanisms. However, under certain conditions, such as UV-radiation or metabolic dysfunction, the ROS can be generated excessively to overwhelm the natural defense capabilities of the body [5]. Thus a situation of oxidative stress occurs, in which biomolecules (proteins, lipids, and nucleic acids) can suffer oxidative damage, causing tissue injury and degenerative diseases [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During normal oxidative metabolism, the ROS are formed in small quantities and can be removed effectively by natural defense mechanisms. However, under certain conditions, such as UV-radiation or metabolic dysfunction, the ROS can be generated excessively to overwhelm the natural defense capabilities of the body [5]. Thus a situation of oxidative stress occurs, in which biomolecules (proteins, lipids, and nucleic acids) can suffer oxidative damage, causing tissue injury and degenerative diseases [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…OH radical from living organisms, is becoming increasingly recognized. Antioxidants usually act by supplying the highly unstable free radical molecules with electrons, thus preventing or limiting chain reactions that cause tissue damage [5]. This improves general health, helps cell rejuvenation and prevents cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants play a major role in protecting biological systems against many incurable diseases. Antioxidants have been widely used in different fields of industry and medicine as substances which interrupt radical-chain oxidation processes, improve general health, help cell rejuvenation, and prevent cancer [2]. This work offers new approach to the determination of antioxidant and biological activity of biologically active substances (BAS).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been confirmed that, under stress conditions such as the intake of drugs, the action of UV radiation or metabolic dysfunctions, these ROS can be generated in sufficient amounts, as to exceed the normal antioxidant defense capabilities of the organism, causing the oxidation of biomolecules and the initiation of radical chain oxidation in tissues [11,12]. Under these circumstances, antioxidants present in diet retard radical chain oxidation, and, to achieve this goal, they intervene in the initiation or propagation steps [7,13,14].…”
Section: Introduction To Oxidative Stress and Antioxidantsmentioning
confidence: 99%